Literature in the language classroom : - Collie, Joanne (Cambridge University, 1987)
The book is divided into three sections:Part A discusses the questions: Why teach literature? What should we teach? How should we teach it? Part B outlines and illustrates a wealth of student-cented class and homework activities appropriate to each stage of the study of literary work. Part C demonstrates techniques for working with complete texts, and shows how the activities outline in Part B can be applied to particular novels, plays, short stories and poems